Can Patient Experience with Service Quality Predict Survival in Colorectal Cancer?. Issue 6 (22nd August 2012) - Gupta, Digant; Lis, Christopher G.; Rodeghier, Mark
Abstract Despite the recognized relevance of symptom burden in colorectal cancer, there has been limited exploration of whether an individual patient's assessment of the overall quality‐of‐care received might influence outcome. We evaluated the relationship between patient‐reported experience with service quality and survival in 702 returning colorectal cancer patients treated at our institution between July 2007 and December 2010. Overall patient experience "considering everything, how satisfied are you with your overall experience?" was measured on a 7‐point Likert scale ranging from completely dissatisfied to completely satisfied. It was dichotomized into two categories: top box response (7) versus all others (1–6). Cox regression was used to evaluate the association between patient experience and survival. Of 702 patients, 506 were "completely satisfied" while 196 were not. On univariate analysis, "completely satisfied" patients had a significantly lower risk of mortality compared to those "not completely satisfied" (hazard ratio [HR] = 0.78; 95% confidence interval [CI]: 0.61–0.98; p = .04). Similarly, on multivariate analysis controlling for stage at diagnosis, treatment history, age, and gender, "completely satisfied" patients demonstrated significantly lower mortality (HR = 0.74; 95% CI: 0.58–0.95; p = .02). Patient experience with service quality was an independent predictor of survival in colorectal cancer, a novel finding in the literature.